Effect of EDTA on canine parthenote development during in vitro culture - Haeyun Jeong; Minghui Zha; Jin-Gu No; Imran Ullah; Whi-Cheul Lee; Hayeon Wi; Sun A Oc; Tai-young Hur; Jae-Seok Wo; Gi-sun Im; Jong-Gug Kim; Seunghoon Lee (The Korean Society of Animal Reproduction and Biotechnology, 2018)
Somatic cell nuclear transfer (SCNT) is a useful biotechnological tool for animal cloning. Until now, SCNT has been inefficient, especially in dog. It is believed that an embryo developmental block in SCNT embryos is cause of low production efficiency. However, no studies have been performed on canines for embryo developmental block. In this study, we attempted to evaluate the beneficial role of EDTA in canine parthenogenic (PA) embryos development to overcome embryo developmental block. The PA embryos were divided into 0.01 mM EDTA treated and non-treated groups. Embryo developmental efficiency was measured by activating chemically parthenote. After EDTA induction, PA embryos were evaluated for embryonic development, Reactive Oxygen Species (ROS) activity, mitochondrial integrity, ATP production and genomic activation. The EDTA treated PA embryos showed significantly higher survival rate and improved cavity formation compared to non-treated. Furthermore, cytoplasmic ROS level was mitigated and mitochondrial membrane potential was found significantly higher in EDTA treated group followed by higher ATP production. Moreover, major embryonic genomic activation specific markers/factors were also elevated in EDTA treated group. Conclusively, we elucidated that EDTA showed substantially positive effect to overcome embryo developmental block in canine.